Perancangan Sistem Pemantauan dan Pengendalian Debit Air Menggunakan Kontrol PID - Wulan Tika, Shovyana; Baqaruzi, Syamsyarief; Muhtar, Ali (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2021)
Water is an important component in life, but there are still many people who still do not care about the use of water in everyday life. Water use in the household is still very difficult to manage in the use of water effectively. To deal with these problems, of course, a control system is needed that can monitor and control the discharge of water that takes place in real time and programmatically in order to improve the effectiveness of water use. This study developed an Internet of Things (IoT) based Home Water Flow Monitoring (HEROIG) system. The hardware used as the microcontroller of this system is NodeMCU. Water flow sensors are used as sensing resulting from water discharge and servo motors as the main actuator controls on this system. The system is designed using PID control to produce water discharge output according to the user's wishes. Testing of pid control system is done using several experiments input parameter values Kp, Ki and Kd. From the test results that produce the best value when Kp = 1, Ki = 1 and Kd = 0.5. From the design results obtained, also conducted tests on each set point value to produce water discharge output according to user input. The results showed there was still an overshoot condition and had an error value of <14%.